Mean queue time approximation for multi-class tandem queues - Ng, Alphonsus Darren Yong Kit. (2013)
People come into contact with queues on a daily basis. The fundamental structure of a queueing network is a tandem queue. In banks and theme-parks, priority queues are present for customers who pay a higher premium. However, we do not know how much time savings the higher priority customers really have. In this paper, the performance of a non-preemptive G/G/1 queueing system with two priorities is analyzed. By assuming Poisson arrivals and Gamma distributed service times, simulations with variations in inter-arrival times as well as service times will be carried out to study the performance of a multi-class tandem queue. The characteristics of intrinsic ratio, which is a newly found approach by Associate Prof Wu Kan for approximating tandem queues, will also be thoroughly examined to see if its properties remain constant in a multi class tandem queue setting.